Linking smallholder vegetable producers to markets - A comparison of a vegetable producer group and a contract-farming arrangement in the Lushoto District of Tanzania. (October 2018) - Gramzow, Andreas; Batt, Peter J.; Afari-Sefa, Victor; Petrick, Martin; Roothaert, Ralph
Abstract: For several decades there has been a growing interest in institutional arrangements to link smallholder farmers to markets. In particular, registered farmer organizations and contract farming arrangements have been very common approaches that have been used to integrate smallholder farmers into agricultural value chains. This study compares a farmer-based organization and a contract farming approach, both of which are active in the same geographic location and operate under the same economic and social constraints. While concentrating our analysis on four critical factors (group homogeneity, size and ability to cope with "free-riding" behavior; supplier-buyer contract enforcement; access to external services; and the supportive role of the government and NGOs), we investigate: (a) how both approaches tackle the same problems, constraints and shortcomings; (b) which structural weaknesses limit their performance in linking smallholder farmers to formal markets; (c) what support measures may facilitate the sustainability of those approaches; and (d) which approach is more suitable to respond quickly to changing market conditions? The registered tight farmer-based organization benefits from a high degree of trust among members enabling them to purchase joint assets, remain independent from single buyers, and maintain an informal quality control system. The advantage of the contract farming approach lies in the formal quality control mechanisms, which reduce the necessity for high group cohesion and allows them to include resource-poor farmers as members. Conversely, formal quality control requires high start-up funding that cannot, in most cases, be borne by the group members and thus requires investment from single buyers, governments or donors, which can create dependencies. Government interventions in terms of capacity building programs for second-tier organizations could allow farmer groups to share the costs associated with input provision, capacity building and extension services. Public-private partnerships providing certification at lower costs may allow farmer groups to reduce dependencies on single buyers. Highlights: Impact of contract farming and farmer-based organizations on smallholder farmers' marketing activities. Advantages and disadvantages of formal and informal quality control systems in smallholder agriculture. Potential interventions to support arrangements aiming at linking smallholder farmers to markets.